Analysis of research and community service trends at the Faculty of Administrative Sciences, Brawijaya University, 2020-2024 - Suryadi Suryadi; Latifah Hanum; Damas Dwi Anggoro; Hefry Johan Ferdhianzah (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This study aims to analyze research and community service trends at the Faculty of Administrative Sciences, Brawijaya University (FIA UB) for the 2020–2024 period and evaluate their compliance with the Research and Community Service Master Plan (RIPP). The method used is a systematic literature review (SLR) with a qualitative descriptive approach based on research and community service reports of FIA UB lecturers mapped according to the roadmap themes of each study program. Data were analyzed based on lecturer names, research titles, roadmap themes, years, and student involvement. The study results show that the majority of research and community service activities are in accordance with the FIA UB RIPP roadmap, although there are discrepancies in several study programs, particularly the Bachelor of Taxation and Master of Higher Education Management. Overall, there were 974 conformities and 590 non-conformities in research and community service topics. In terms of student engagement, participation has shown a significant increase each year, with a total of 777 conformities, 116 non-conformities, and 80 activities without student involvement. These findings underscore the importance of faculty and student synergy in producing research and community service programs relevant to community needs and the development of administrative science. The study recommends strengthening monitoring and evaluation (M&E) mechanisms on a regular basis to ensure consistency with the roadmap and the relevance of student involvement. Thus, the results of FIA UB's research and community service programs are expected to increasingly contribute to achieving the faculty's and university's strategic goals and addressing current societal issues